Brucella placentitis and seroprevalence in northern fur seals (Callorhinus ursinus) of the Pribilof Islands, Alaska. (July 2014) - Duncan, Colleen G.; Tiller, Rebekah; Mathis, Demetrius; Stoddard, Robyn; Kersh, Gilbert J.; Dickerson, Bobette; Gelatt, Tom
Brucella species infect a wide range of hosts with a broad spectrum of clinical manifestations. In mammals, one of the most significant consequences of Brucella infection is reproductive failure. There is evidence of Brucella exposure in many species of marine mammals, but the outcome of infection is often challenging to determine. The eastern Pacific stock of northern fur seals (NFSs, Callorhinus ursinus ) has declined significantly, spawning research into potential causes for this trend, including investigation into reproductive health. The objective of the current study was to determine if NFSs on St. Paul Island, Alaska have evidence of Brucella exposure or infection. Archived DNA extracted from placentas ( n = 119) and serum ( n = 40) samples were available for testing by insertion sequence (IS) 711 polymerase chain reaction (PCR) and the Brucella microagglutination test (BMAT), respectively. As well, placental tissue was available for histologic examination. Six (5%) placentas were positive by PCR, and a single animal had severe placentitis. Multilocus variable number tandem repeat analysis profiles were highly clustered and closely related to other Brucella pinnipedialis isolates. A single animal was positive on BMAT, and 12 animals had titers within the borderline range; 1 borderline animal was positive by PCR on serum. The findings suggest that NFSs on the Pribilof Islands are exposed to Brucella and that the organism has the ability to cause severe placental disease. Given the population trend of the NFS, and the zoonotic nature of this pathogen, further investigation into the epidemiology of this disease is recommended.